230k views
1 vote
Solve each system using the elimination method 2x + y = 3 -2x + 5y = -9

User Ken Paul
by
5.2k points

1 Answer

0 votes
The 2X and negative 2X cancel out. Then you add the 3 to the -9 to get -6 they you add the lonely Y to the 5Y so now you have 6Y=-6. Then you divide them both by 6 to get the Y alone. 6Y = 6
— —
6 6

So then it’s Y=1. There you go. Hope I helped!!!
User Blizzardengle
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.